a) x∈ (-∞;3)
b) x∈ (-∞;0] ∪ [4;+∞)
c) x∈ (-∞;0)∪(0;2/3)
d) x∈ [-1/2;1) ∪ (1;+∞)
Объяснение:
a) f(x)=√(-x+3);
-x+3≥0; -x≥-3; x≤3.
ОО: x∈(-∞;3).
b) f(x)=√(0,5x²-2x); 0,5x²-2x≥0; x(0,5x-2)≥0;
x≥0;
0,5x-2≥0; x≥2/0,5; x≥4; x∈[4;+∞);
x≤0;
0,5x-2≤0; x≤2/0,5; x≤4; x∈(-∞;0];
OO: x∈(-∞;0] ∪ [4;+∞);
c) f(x)=ln(2/x-3);
2/x-3>0; 2/x>3; x<2/3; x∈(-∞;2/3);
x≠0; x∈(-∞;0)∪(0;+∞)
OO: x∈(-∞;0)∪(0;+∞) ∩ (-∞;2/3) ⇒ x∈(-∞;0)∪(0;2/3)
d) f(x)=√(3/(x-1)+2);
3/(x-1)+2≥0; 3+2(x-1)≥0; x≥-1/2; x∈[-1/2;+∞)
x-1≠0; x≠1; x∈(-∞;1)∪(1;+∞)
OO: x∈[-1/2;+∞) ∩ (-∞;1)∪(1;+∞) ⇒ x∈[-1/2;1)∪(1;+∞)
{xy+x+y=11; {xy+x+y=11;
{x²y+xy²=30. ⇒ {xy(x+y)=30.
Пусть х+у=u; xy=v
{v+u=11;
{vu=30.
Решаем систему подстановки:
{v=11-u;
{(11-u)u=30.
Решаем второе уравнение системы
u²-11u+30=0
D=(-11)²-4·30=121-120=1
u₁=(11-1)/2=5 или u₂=(11+1)/2=6
v₁=11-u₁=11-5=6 или v₂=11-6=5
Обратная замена
{x+y=5 или {x+y=6
{xy=6 {xy=5
{y=5-x {y=6-x
{x(5-x)=6 {x(6-x)=5
Решаем вторые уравнения систем:
x²-5x+6=0 x²-6x+5=0
D=25-24=1 D=36-20=16
x₁=(5-1)/2=2; x₂=(5+1)/2=3 x₃=(6-4)/2=1; x₄=(6+4)/2=5
y₁=5-2=3; y₂=5-3=2 y₃=6-1=5; y₄=6-5=1
О т в е т. (2;3) (3;2) (1;5) (5;1).
так?
Объяснение: